DUNIA SENI RUPA INDONESIA: KRITIK SENI PAMERAN LIKE/DISLIKE - Putri, Malena Wati; Nagara, Martien Roos (ATRAT: Jurnal Seni Rupa, 2024)
Art is one of the important aspects in various facets of human life, therefore art exhibitions serve as crucial platforms for artists to interact with art enthusiasts and convey their artistic messages. Art exhibitions play a significant role in the development of visual arts in Indonesia. In this study, the author will examine, elaborate, and critique a solo exhibition by Taat Joeda titled “Like/Dislike” held at the Bandung Center for Culture Gallery. This research method involves direct observation or visitation to the exhibition and an overall analysis using art critique methods and mechanisms. The findings of the study reveal that the “Like/Dislike” art exhibition presents a refreshing approach in its theme about the tangle of undergrowth and captivating painting techniques. In conclusion, this research highlights the overall depth of the “Like/Dislike” exhibition with its theme “The Beauty Hidden Within the Thicket.”